DIGITALIZATION IMPLEMENTATION IN LEARNING AND SCHOOL MANAGEMENT: A QUALITATIVE STUDY AT SMA ISLAM HIDAYATULLAH SEMARANG - Chory Praseptiana; Widya Kusumaningsih; Nurkolis Nurkolis (SOSIOEDUKASI, 2026)
This study aims to analyze the implementation of digitalization in learning and school management at SMA Islam Hidayatullah Semarang. The research employed a qualitative descriptive approach to explore in depth the processes, challenges, and impacts of digitalization within the school context. Data were collected through in-depth interviews, participant observation, and document analysis involving the principal, teachers, IT staff, and students as key informants. The findings indicate that digitalization has been systematically implemented through the use of Learning Management Systems (LMS), digital learning media, and technology-based assessment, which enhance learning flexibility, accessibility, and student engagement. In terms of school management, digitalization has improved administrative efficiency, data integration, and communication transparency. However, several challenges were identified, including limited digital competence among some teachers, variations in students’ digital literacy, and infrastructural constraints such as unstable internet access. Despite these challenges, the overall response of school stakeholders was positive, reflecting a strong institutional commitment to digital transformation. This study concludes that effective digitalization requires not only technological readiness but also continuous capacity building, institutional support, and adaptive organizational culture to optimize its impact on educational quality.